2018
DOI: 10.1126/sciadv.aau3488
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence-induced jumping of droplets on superomniphobic surfaces with macrotexture

Abstract: Superomniphobic surfaces with macrotextures allow coalescence-induced jumping of droplets at Ohnesorge number >1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 42 publications
1
111
0
Order By: Relevance
“…In section 2.2, we have defined the surface energy and the kinetic energy. Based on these discussions, we denoted the initial surface energy as Esurf,i , Esurf,i = Ai, the surface energy when the droplet departs from the surface 38 where Ai is the initial surface area of two droplets and Ad is the surface area when the droplet departs from the surface. The energy conversion rate can be obtained according to the following formula.…”
Section: Energy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In section 2.2, we have defined the surface energy and the kinetic energy. Based on these discussions, we denoted the initial surface energy as Esurf,i , Esurf,i = Ai, the surface energy when the droplet departs from the surface 38 where Ai is the initial surface area of two droplets and Ad is the surface area when the droplet departs from the surface. The energy conversion rate can be obtained according to the following formula.…”
Section: Energy Analysismentioning
confidence: 99%
“…Designing special structures to enhance jumping is also a hot topic in this field. Both Wang et al 37 and Vahabi et al 38 set ridges between two droplets on a smooth superhydrophobic surface, and concluded that the droplet jumping height as well as the energy conversion rate increased significantly comparing with jumping on a superhydrophobic surface without a ridge.…”
Section: Introductionmentioning
confidence: 99%
“…To our surprise, the model captures space-time symmetry-breaking motions observed in real drops and may anticipate nonlinear behavior like torus dynamics and droplet jumping, currently under active study for real drops [19].…”
Section: Resultsmentioning
confidence: 93%
“…Superomniphobic surfaces are extremely repellent to and display negligible adhesion with virtually all contacting liquids, having high or low surface tension . Such high liquid repellency and negligible adhesion, which lead to high droplet mobility on the surface, have attracted tremendous interests in wide variety of applications such as self‐cleaning, chemical shielding, corrosion resistance, water energy harvesting, membrane separation, and lab‐on‐chip devices . As such, superomniphobic surfaces have been fabricated on numerous substrates such as metals, polymers, glass, and paper .…”
mentioning
confidence: 99%